Geodetically estimated location and geometry of the fault plane involved in the 2018 Hokkaido Eastern Iburi earthquake - Tomokazu Kobayashi; Kyonosuke Hayashi; Hiroshi Yarai (Earth, Planets and Space, 2019)
Abstract By applying the InSAR method to ALOS-2 SAR data acquired before and after the 2018 Hokkaido Eastern Iburi earthquake, the ground displacement fields were successfully mapped. Ground deformation is distributed on the eastern side of an active fault, known as the Ishikari-Teichi-Toen fault zone (ITTFZ). Uplift of up to ~ 7 cm is distributed throughout the source region, and eastward movement of up to ~ 4 cm is widely observed on the eastern side of the source region. The fault model constructed by inverting InSAR and GNSS data under an assumption of a uniform slip on a rectangular fault plane shows reverse fault motion on a plane dipping eastward at 74°. The fault top is positioned around a depth of 15 km, suggesting that the slip significantly occurs deeper than the typical seismogenic zone for the Japanese island. The fault plane is at a relatively high dip angle, and the shallow extension of the estimated fault plane does not connect to any known surface traces of the ITTFZ. This may suggest that the fault involved with the 2018 event is physically separated from the ITTFZ, or that the fault plane bends to a lower dip angle at a shallow crustal depth. The fault rupture area is located in a spatially inhomogeneous seismic velocity structure field and the main slip occurs at the western edge of a low Vp area which vertically thickens on the eastern side of the fault. This may suggest that the 2018 earthquake occurred at seismic velocity boundary. An estimate of Coulomb Failure Function change suggests that the static stress change due to the 2018 event can promote reverse fault slip on the southern part of the ITTFZ.